Knowledge vs Practice: Malaria Chemoprophylaxis Use among Travelers in South Bali - Kadek Sariani; Kadek Agus Suryada; Anak Agung Sagung Putri Charmenita; Cokorda Gede Bagus Muladhara Cakra K.; Ni Kadek Meta Jayanti; Putu Indah Budiapsari (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: Malaria remains a significant global health problem with increasing cases and deaths every year. Travelers visiting endemic areas, especially those classified as Visiting Friends and Relatives (VFR), have a high risk of malaria infection due to a lack of awareness and compliance with chemoprophylaxis. The use of malaria chemoprophylaxis among international travelers in Bali is limited, so the low chemoprophylaxis use among travelers must be evaluated based on knowledge levels. Purposes: To determine the level of knowledge about the use of malaria chemoprophylaxis and analyze the distribution of its use among foreign and domestic tourists in South Bali. Methods: This cross-sectional study used a survey conducted at Mertasari Beach, Sanur Beach, Kuta Beach, and Jimbaran Beach. Consecutive sampling of 106 foreign and domestic tourists using a questionnaire validated by r count > r table by Pearson Correlation by SPSS version 27. Results: A total of 51% of respondents had a good level of knowledge, 41.5% were sufficient, and 10.4% were deficient. However, only 9.4% of travelers used malaria chemoprophylaxis, while 90.6% did not. Conclusion: Although travelers' knowledge of malaria chemoprophylaxis was high, their use of it was low, indicating a gap between knowledge and preventive practices. Therefore, more effective educational strategies and efforts are needed to increase compliance with malaria chemoprophylaxis among travelers.